Does it Make a Difference? Comparing Growth Effects of European and North American FDI in Latin America - Gabriele Tondl; Patricia Prüfer (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2007)
FDI from the European Union (EU) ranks before FDI from North America (NA) in some of the Latin American countries. We investigate the impact of EU- versus NA-FDI on the growth rate including about 50 controls. Country specific effects and parameter heterogeneity are incorporated in our estimation. We use Bayesian Model Averaging to address model uncertainty and to select the best models and most robust parameters. Our results indicate that positive effects of FDI are dependent on the functioning of legal frameworks and the quality of infrastructure. EU-FDI is an important, robust growth determinant whereas NA-FDI is not.
Keywords: F43; O54; C52; F21; 330; Growth determinants; FDI; model uncertainty; Bayesian Model Averaging; Latin America